Does Economic Integration Affect Inequality in Developing Countries? Evidence from a Global Sample - Tung, Le Thanh; Thang, Pham Nang; Uyen, Lam Tu (European Journal of Sustainable Development, 2020)
Economic integration plays an important role in promoting economic growth. However, it can also increase inequality, although the relationship between economic integration and inequality is still unclear. Our paper aims to study the impact of economic integration on income inequality with a global sample regarding 59 developing countries collected from 1996-2016. Besides, we divide the overall sample into three smaller examples including developing countries in Asia, Africa, and Latin-America. Unlike previous studies, our research results confirm that economic integration has a multidimensional impact on inequality in countries. In detail, trade openness can help to reduce inequality, however, foreign direct investment increases inequality during the study period. The Kuznets' inverted-U curve among income and inequality is confirmed in the cases including the overall sample, Asia and Africa, excluding for the Latin-America. Finally, technology development and remittances are found to play a negative impact on inequality, while inflation leads to an increase in inequality level in developing countries. Keywords: economic integration, inequality, trade openness, FDI, Kuznets, developing country